GAMBARAN TERAPI DIABETES DENGAN PENYAKIT PENYERTA HIPERLIPIDEMIA DI RUMAH SAKIT - Refdanita Refdanita; Lili Musnelina; Teodhora Teodhora; Hirim Hotma Uli Aprianis (LLDIKTI Wilayah X, 2021)
Diabetes mellitus and cholesterol disorders are a lethal combination that places patients with diabetes 2-4 times more at risk for developing macrovascular and microvascular complications. Risk factors for Diabetes with Hyperlipidemia include age, sex, lifestyle, metabolic conditions that affect the metabolism of plasma lipoproteins, insulin deficiency. This study aims to know determine demographic data (age, sex, and length of stay), to know results of the laboratory tests and to know description of the therapy. The study was conducted descriptive with a cross sectional design, retrospective data collection methods from patients medical records of diabetic with hyperlipidemia at the hospital inpatient installation in January-December 2019, with 130 sample patients medical record. Result presented as a percentage table. The mean results of the study based on the highest patients demographics were at age 51-60 years as 40%, the highest gender was females 56%, based on the highest length of stay was 3 days 54%. Initial fasting glucose examination with the highest percentage >126 mg / dl of 78.5%. Total cholesterol examination with the highest percentage >200 mg / dl was 84.6%, triglycerides with the highest percentage >150 mg / dl was 15.4%, LDL with the highest percentage >100 mg / dl 79.3%. The highest use of oral antidiabetic was 52.30%, long-acting insulin was 40.70% and oral antihyperlipidemia was 77.60%. The statin class has been shown to have an effect in preventing complications in patients with type 2 diabetes mellitus